Implementation of Team Games Tournament Model Assisted by Audio-Visual Media to Improve Student Learning Outcomes in Islamic Education Learning at SMP Negeri 1 Samatiga - Narima, Sri; Iqlima (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to determine the effectiveness of the application of a Team Games Tournament (TGT) type cooperative learning model assisted by audio-visual media in improving student learning outcomes in Islamic Religious Education subjects at SMP Negeri 1 Samatiga. The method used is Classroom Action Research (PTK) with class VIII research subjects totaling 32 students. The research was carried out in two cycles, each cycle consisted of planning, implementation, observation, and reflection. Data collection instruments are in the form of learning outcome tests, observation sheets of teacher and student activities, and interviews. The results showed a significant improvement in student learning outcomes after the application of the TGT model with audio-visual media. In the initial condition, the percentage of students who completed their studies reached 53.1%, then increased to 75% in the first cycle, and reached 87.5% in the second cycle. This shows that the TGT type cooperative learning model supported by audio-visual media is effective in improving the learning outcomes of Islamic Religious Education. Thus, the application of this model can be used as an alternative learning strategy that is able to increase student motivation and learning outcomes optimally.